Circulating immune-complexes of IgG/IgM bound to B2-glycoprotein-I associated with complement consumption and thrombocytopenia in antiphospholipid syndrome - Naranjo, Laura; Stojanovich, Ljudmila; Djokovic, Aleksandra; Andreoli, Laura; Tincani, Angela; Maślińska, Maria; Sciascia, Savino; Infantino, Maria; Garcinuño, Sara; Kostyra-Grabczak, Kinga; Manfredi, Mariangela; Regola, Francesca; et al. (Frontiers in Immunology, 2022)
Background. Antiphospholipid syndrome (APS) is a multisystemic autoimmune disorder characterized by thrombotic events and/or gestational morbidity in patients with antiphospholipid antibodies (aPL). In a previous single center study, APS-related clinical manifestations that were not included in the classification criteria (livedo reticularis, thrombocytopenia, leukopenia) were associated with the presence of circulating immune-complexes (CIC) formed by beta-2-glycoprotein-I (B2GP1) and anti-B2GP1 antibodies (B2-CIC). We have performed a multicenter study on APS features associated with the presence of B2-CIC. Methods: A multicenter, cross-sectional and observational study was conducted on 303 patients recruited from six European hospitals who fulfilled APS classification criteria: 165 patients had primary APS and 138 APS associated with other systemic autoimmune diseases (mainly systemic lupus erythematosus, N=112). Prevalence of B2-CIC (IgG/IgM isotypes) and its association with clinical manifestations and biomarkers related to the disease activity were evaluated. Results. B2-CIC prevalence in APS patients was 39.3%. B2-CIC-positive patients with thrombotic APS presented a higher incidence of thrombocytopenia (OR: 2.32, p=0.007), heart valve thickening and dysfunction (OR: 9.06, p=0.015) and triple aPL positivity (OR: 1.83, p=0.027), as well as lower levels of C3, C4 and platelets (p-values: <0.001, <0.001 and 0.001) compared to B2-CIC-negative patients. B2-CIC of IgM isotype were significantly more prevalent in gestational than thrombotic APS. Conclusions. Patients with thrombotic events and positive for B2-CIC had lower platelet count and complement levels than those who were negative, suggesting a greater degree of platelet activation.